Information Systems Applications on The Organizational Level - Meiryani; Sudrajat, Jajat; Daud, Zaidi Mat; Yanti (International Journal of Psychosocial Rehabilitation, 2020)
Management can be divided into three levels, namely the lower level (operational level), intermediate level (tactical level) and upper level (strategic level). Because each level of management performs different activities, they also need different information. Because the information needed is different, the information system used is also different. Information systems at the operating level support operations managers to carry out their activities. The main purpose of information systems at this level is to answer routine questions for the purpose of controlling the flow of transactions that occur in the organization. Information systems include expert systems (SP) or expert systems (ES), artificial neural networks (JNB) or artificial neural networks (ANN), decision support systems or decision support systems (DSS) or group support systems (DSS) GSS), geographic information systems (GIS) or geographic information systems (GIS). Information system at the top level used for strategic planning and problem solving. Information systems at this strategic level are executive information systems (SIE) or executive information systems (EIS) or executive support systems (ESS). Information systems that connect to three management levels are office automation systems (SOK) or office automation systems (AOS).